Determinants of online marketing channel choice among small and micro community enterprises in Thailand - Rapankum, Narawut; Konkan, Thanada; Srilapat, Chanoknan; Khodmechai, Kumaree; Niljinda, Kanjanaporn; Lertjunthuk, Laddawan (Tarım Ekonomisi Derneği, 2025)
Purpose: This study aimed to analyze the factors affecting the decision of small and micro community enterprises (SMCEs) in Sakon Nakhon Province, Thailand, to engage in online product marketing. Design/Methodology/Approach: A structured questionnaire was distributed to 360 SMCEs across 18 districts in 2024 to collect empirical data. The survey data were analyzed via 12 variables (gender, age, education, experience, marketing training, attitude, group size, product variety, product type, marketing budget, distance, and technology equipment) using descriptive statistics and binary logistic regression. Findings: Approximately 66% of the SMCEs marketed their products using online and offline channels, with the majority selecting social media platforms (Facebook and Line) as key channels and the minority using e-marketplaces (Shopee and Lazada). Group management experience, group leader attitude, product variety, product type, marketing budget, and distance from the shipping company proved to be the statistical factors influencing the decision to sell products online. Originality/Value: This study informs the development of targeted online marketing strategies that cater to diverse target groups’ product attributes and resources. Furthermore, the elicited outcomes can assist in formulating policies or establishing training that strengthens farmer groups’ potential to enhance their competitiveness in the agricultural market. Small-scale entrepreneurs can enhance their competitiveness in online markets with the strategic decision-making information derived from this study.

Amaç: Bu araştırmanın amacı, Tayland'ın Sakon Nakhon Eyaletindeki mikro, küçük ve orta ölçekli işletmelerin (KOBİ) ürünlerini çevrimiçi pazarlamaya yönelik kararlarını etkileyen belirleyicileri incelemektir. Tasarım/Metodoloji /Yaklaşım: Veriler 2024 yılında 18 ilçede 360 KOBİ'ye yapılandırılmış bir anket uygulanarak toplanmıştır. Verileri analiz etmek için tanımlayıcı istatistikler ve ikili lojistik regresyon. Analizde toplam cinsiyet, yaş, eğitim, deneyim, pazarlama eğitimi, tutum, grup üyeleri, ürün çeşitliliği, ürün tipi, pazarlama bütçesi, mesafe ve teknoloji ekipmanı olarak 12 değişken kullanılmıştır. Bulgular: SMCE'lerin %66'sının ürünlerini hem çevrimiçi hem de çevrimdışı kanallar aracılığıyla pazarladığını ortaya. Çoğunluk, birincil kanalları olarak Facebook ve Line gibi sosyal medya platformlarını tercih etti, ancak azınlık bir grup Shopee ve Lazada gibi e-pazar yerlerini. Ürünleri çevrimiçi satma kararını etkileyen istatistiksel faktörler, grup yönetimi deneyimi, grup liderinin tutumu, ürün çeşitliliği, ürün türü, pazarlama bütçesi ve nakliye şirketine olan uzaklık olarak ortaya konmuştur. Özgünlük/Değer: Bu çalışma, her hedef grubun ürün özellikleri ve kaynaklarına uygun çevrimiçi pazarlama stratejileri geliştirmek için içgörüler sunar. Ayrıca, çiftçi gruplarının tarımsal ürün pazarlarındaki rekabet güçlerini artırma potansiyellerini güçlendirmek için politikalar belirlemek veya eğitimler düzenlemek için de kullanılabilir. Ayrıca, küçük ölçekli girişimcilere çevrimiçi pazarlardaki rekabet güçlerini artırmak için stratejik karar alma bilgileri sağlar.
Tayland'daki küçük ve mikro topluluk işletmeleri arasında çevrimiçi pazarlama kanalı seçiminin belirleyicileri
Keywords: Marketing in Agricultural Management; Tarımsal Yönetimde Pazarlama